PSYCHOLOGICAL REALISM IN ENGLISH AND UZBEK LITERARY TRADITIONS - Djalaldinova Malohat Zuxurdinovna, (TADQIQOTLAR, 2026)
Abstract This article examines the artistic interpretation of psychological realism within the  landscapes  of  the  human  psyche,  tracing  the  evolution  of  realism  and  its psychologically  oriented  dimension  in  world  and  Uzbek  literature.  Realism,  which emerged in the nineteenth century as a reaction against Romanticism, sought to depict life  with  verisimilitude,  objectivity,  and  socio-historical  precision.  Psychological realism  developed  as  one  of  its  most  intricate  branches,  foregrounding  the  inner mechanisms of consciousness, emotional experience, and cognitive processes. Drawing  on  examples  from  the  works  of  Fyodor  Dostoevsky,  Henry  James, Virginia Woolf, Marcel Proust, James Joyce, and William Faulkner, the study explores narrative  strategies  such  as  interior  monologue  and  stream  of  consciousness  as aesthetic instruments for representing subjective experience. It further analyzes the development of psychological realism in Uzbek literature through the prose of Abdulla Qodiriy,  Cho‘lpon,  and  Asqad  Muxtor,  demonstrating  how  psychological  inquiry became  central  to  the  artistic  exploration  of  identity,  moral  conflict,  and  social transformation.